Development of Waterfalls and Penikit Hot Springs Tourism Objects in Belok Sidan Village - Nyoman Dwika Ayu Amrita; Agus Wiryadhi Saidi; Made Mulia Handayani (Universitas Pendidikan Ganesha, 2022)
The attraction of Penikit Waterfall is unique, which is known as a hot and cold waterfall. However, the development of Penikit Waterfall tourism has not sufficiently affected the economy of the local community. The lack of visitors and the lack of information in the wider community about the place is one of the weaknesses of this tourist attraction. In addition, the infrastructure at this tourist attraction is still lacking. For this reason, it is necessary to hold a PKM for the development of Penikit Waterfalls and Hot Springs in Belok Sidan Village, Petang District, Badung Regency. The target partner in this PKM is the Tourism Awareness Group (Pokdarwis) Wana Giri, totaling 33 people. The PKM activities carried out are, repairing toilets (structural work and finishing work), installing clean water for toilets, parking lot cleaning, hardening and cementing hot water pools, making WEB, training on using WEB and simple bookkeeping. The results of the PKM program on the Penikit Waterfall and Hot Springs help increase the economic potential that supports development in the Penikit area in particular, namely: there are business opportunities, there is an increase in income, and there is labor absorption.